External Faktor Eksternal Berpengaruh dengan Sisa Makanan (Nabati dan Sayur) pada Diet Makanan Biasa dan Lunak di RSUD Harapan dan Doa Kota Bengkulu - Putricia, Dita; Yuliantini, Emy; Wahyudi, Anang (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Research data from Harapan and Doa Hospital in 2019 showed that the remaining vegetable protein increased to 27.61% and vegetables 56%. This rate still exceeds the minimum hospital service rate for food waste, which is ≤ 20%. Purpose of the study was to examine external factors that affect the remaining plant and vegetablefood in the diet of ordinary and soft foods as well as an overview of external factors at Harapan and Doa Hospital, Bengkulu City. Method: Cross sectional design with the type of analytic survey research used in this study with a sample of 34 respondents. Results: In the remaining vegetable side dishes, timeliness of feeding with a p-value of 0.648, food taste (0.182) and the attitude of the serving staff (0.487) which means that H0 failed to be rejected (> 0.05). For leftover vegetable food, the timeliness of feeding with a p-value of 0.647, the atmosphere of the caring environment (0.541) and the attitude of the serving staff (1.000) which means that H0 failed to be rejected (> 0.05). Conclusion: There is a relationship between the appearance of food and the consumption of food from the outsidewith vegetable and vegetable side dishes.es.